A novel protein‐based autologous topical serum for skin regeneration. (9th August 2019) - Anitua, Eduardo; Troya, María; Pino, Ander
Abstract: Background: As skin ages, a functional decrement occurs. To avoid future vulnerability to dermatologic diseases, an optimal cutaneous regeneration is mandatory. Biological therapies based on blood‐derived autologous proteins are gaining attention of scientists and dermatologists. Objectives: A novel 100% autologous topical serum has been developed using plasma rich in growth factors technology. The physicochemical characterization and the biologic potential of the novel formulation have been studied. Methods: Rheological and mechanical properties and the biological capacity of the formulation were characterized. Human dermal fibroblast culture and 3D organotypic skin explants were used as in vitro and ex vivo cutaneous models, respectively. Results: The autologous topical serum presented an optimal spreadability index and appropriate shear thinning behavior that allowed an easy handling and rapid integration within the cutaneous tissue. The formulation has a high growth factor load with the ability to progressively penetrate into the dermal/epidermal layers of the skin. It is biocompatible and promotes cell proliferation and chemotactic activity. The autologous topical serum promotes the biosynthetic activity of cells by the stimulation of collagen and hyaluronic acid expression. Conclusions: These findings present an in situ and easy to prepare autologous topical serum based on the patient's own blood with physicochemical and bioactive properties that may be used for skin regeneration purposes.